Sartre was a rock, and eighty years ago Being and Nothingness hit our window pane - Rodrigues, Thiago (Argumentos - Revista de Filosofia, 2025)
This brief essay unpretentiously seeks to highlight the relevance of some of the central questions in Jean-Paul Sartre's Being and Nothingness, thus aiming to contribute to broadening the scope of the French philosopher's ideas. Without fearing controversy, it presents the correlation between the concept of freedom and the responsibility necessarily implied. Such concepts remind us that this work is current, for it demands to assume its political and ethical unfoldings as unavoidable demands. The debate is built, then, through Sartre's encounters with his peers, highlighting the interlocutions and controversial divergences that mark his itinerary. Finally, the timeliness of the work seems to reside in the historical failure of the humanist project, that is, Being and Nothingness continues to be current, because we are still incapable of promoting a historical situation in which the human being is free.